Skeletal Fluorosis: A Case of Inhalant Abuse Leading to a Diagnosis of Colon Cancer - Haseeb Mohideen MD; Dushyant Singh Dahiya MD; Dustin Parsons MSc; Hafsa Hussain BSc; Rizwan Syed Ahmed DO (Journal of Investigative Medicine High Impact Case Reports, 2022)
Skeletal fluorosis is a long-term bone disease that develops when prolonged fluoride toxicity leads to osteosclerosis and bone deformities that result in crippling pain and debility. The disease is endemic to many countries due to environmental or industrial exposures. However, rare cases in the United States have been reported from various causes including heavy toothpaste ingestion, excessive tea consumption, voriconazole use, and inhalant abuse. Here, we present a case of a 41-year-old man who presented for weight loss and severe joint pains due to bony sclerotic lesions found on X-rays. Social history revealed that he had been recreationally inhaling compressed air dusters used for cleaning electronics. Owing to concern for malignancy, he underwent an extensive work-up which led to a diagnosis of colon cancer, but positron emission tomography/computed tomography (PET/CT) and bone biopsy were unexpectedly negative for metastatic bone disease. Further characterization of his lesions by skeletal survey led to a diagnosis of skeletal fluorosis secondary to inhalant abuse. As in this patient, the disease can be difficult for clinicians to recognize as it can be mistaken for various boney diseases such as metastatic cancer. However, once there is clinical suspicion for skeletal fluorosis, various tests to help confirm the diagnosis can include serum and urine fluoride levels, skeletal survey, and bone ash fluoride concentration. Treatment of skeletal fluorosis primarily involves cessation of fluoride exposure, and recovery can take years. Ultimately, further study is required to develop recommendations and guidelines for diagnosis, management, and prognosis of the disease in the United States.